Radioactivity in the Marine Environment: Understanding the Basics of Radioactivity. Issue 1 (27th December 2018) - Benitez‐Nelson, Claudia R.; Buesseler, Ken; Dai, Minhan; Aoyama, Michio; Casacuberta, Núria; Charmasson, Sabine; Johnson, Andy; Godoy, José Marcus; Maderich, Vladimir; Masqué, Pere; Moore, Willard; Morris, Paul J.; et al.
Abstract : Natural and anthropogenic radionuclides are used to study a suite of environmental processes. Yet their applications in aquatic systems are hindered by a general lack of knowledge regarding the underlying concepts of radioactivity, the occurrence of radionuclides in ecosystems, and the equations used to describe their decay mechanisms in environmentally applicable ways. The goal of this lecture is to provide upper level undergraduate and graduate students with a basic understanding of the fundamentals of radiochemistry, including the origin and stability of elements, radioactive decay mechanisms, and the fundamental equations that govern radioactive decay. This lecture is the first of a four‐part lecture series on radionuclides in the marine environment.